Inside Back Cover: Chemoenzymatic Synthesis of Advanced Intermediates for Formal Total Syntheses of Tetrodotoxin (Angew. Chem. Int. Ed. 34/2018). Issue 34 (19th June 2018) - Baidilov, Daler; Rycek, Lukas; Trant, John F.; Froese, Jordan; Murphy, Brennan; Hudlicky, Tomas
Abstract : A chemoenzymatic approach to tetrodotoxin is described by T. Hudlicky and co‐workers in their Communication onpage 10994 ff. Benzyl acetate was subjected to highly regio‐ and enantioselective dihydroxylation mediated by a robust recombinant organism, E. coli JM109 (pDTG601A), that overexpresses toluene dioxygenase. The resulting homochiral diene diol served as an ideal starting material for the enantioselective synthesis of tetrodotoxin. The picture gives a concise summary of this approach, showing that tetrodotoxin can be obtained from marine as well as bacterial sources.